Technical and economic analysis of Brayton-cycle-based pumped thermal electricity storage systems with direct and indirect thermal energy storage. (15th January 2022) - Zhang, Han; Wang, Liang; Lin, Xipeng; Chen, Haisheng
Abstract: Pumped thermal electricity storage (PTES) systems have attracted increasing attention, owing to high energy density, low cost, flexible adjustable energy storage duration, and lack of geographical restrictions. At present, theoretical research for PTES is relatively deep. Further reduction of investment costs is of great value to its development and application. This paper proposes a 10-MW PTES system with indirect thermal energy storage (TES) (I-PTES). The I-PTES and a PTES system with direct TES (D-PTES) are analyzed and compared in terms of their technical and economic performances. The results show that the I-PTES is advantageous owing to its low installation cost when its electricity storage duration exceeds 6 h, despite bearing some loss in round-trip efficiency. For longer-duration electricity storage, the energy capital cost of I-PTES can be lower than 200 $/kWh, i.e., 40% lower than that of D-PTES, whereas the penalty for its round-trip efficiency can be less than 5% after optimization. For a 10-MW I-PTES system, the optimum round-trip efficiency and energy density can reach approximately 65% and 26 kWh/m 3, respectively. This research provides a more economical choice for the long-duration electricity storage, and a theoretical basis for the design and optimization of high-efficiency and low-capital-cost PTES systems. Highlights: An indirect-Brayton-based pumped thermal electricity storage (I-PTES) system was proposed. Technical and economic analyses and comparisons were presented. The I-PTES is economically superior for long-duration electricity storage. The energy capital cost of I-PTES could be 200 $/kWh, i.e., 40% lower than that of direct-PTES. The round-trip efficiency of the I-PTES could reach up to 65%, with an energy density of 26 kWh/m 3 .